Differentially photo-crosslinked polymers enable self-assembling microfluidics - Jamal, Mustapha (2011)
An important feature of naturally self-assembled systems such as leaves and tissues is that they are curved and have embedded fluidic channels that enable the transport of nutrients to, or removal of waste from, specific three-dimensional (3D) regions. Here, we report the self-assembly of photopatterned polymers, and consequently microfluidic devices, into curved geometries. We discovered that differentially photo-crosslinked SU-8 films spontaneously and reversibly curved upon film de-solvation and re-solvation. Photolithographic patterning of the SU-8 films enabled the self-assembly of cylinders, cubes, and bidirectionally folded sheets. We integrated polydimethylsiloxane (PDMS) microfluidic channels with these SU-8 films to self-assemble curved microfluidic networks.